Charge trapping at the dielectric of organic transistors visualized in real time and space - Mathijssen, Simon G. J.; Kemerink, Martijn; Sharma, Abhinav; Cölle, Michael; Bobbert, Peter A.; Janssen, René A. J.; Leeuw, Dago M. de (Advanced materials, 2008)
Scanning Kelvin probe microscopy demonstrates that water-induced charge trapping at the SiO2 dielectric - visualized in real time and space - is responsible for the commonly observed gate-bias-induced threshold-voltage shift in organic field-effect transistors. When a bias is applied to the electrodes, charges are injected onto the SiO2 (see background of the figure). When the contacts are grounded, the charges are released again (foreground picture).
Gesehen am 12.12.2019